2015
DOI: 10.1103/physrevlett.115.247001
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity from Emerging Magnetic Moments

Abstract: Multiorbital Hubbard models are shown to exhibit a spatially isotropic spin-triplet superconducting phase, where equal-spin electrons in different local orbitals are paired. This superconducting state is stabilized in the spin-freezing crossover regime, where local moments emerge in the metal phase, and the pairing is substantially assisted by spin anisotropy. The phase diagram features a superconducting dome below a non-Fermi-liquid metallic region and next to a magnetically ordered phase. We suggest that thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
181
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(198 citation statements)
references
References 40 publications
16
181
0
Order By: Relevance
“…For a fixed total occupation of a given site, the interaction J differentiates between the energies of different orbital occupation and spin states. In a lattice environment, this can lead to considerable shifts in the metal-Mott insulator phase boundaries [2,3], to local moment formation [4], nonlocal correlation effects [5,6], and various types of symmetry breaking [7][8][9][10][11][12][13]. Already in the two-band case, nontrivial crossovers and phase transitions can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…For a fixed total occupation of a given site, the interaction J differentiates between the energies of different orbital occupation and spin states. In a lattice environment, this can lead to considerable shifts in the metal-Mott insulator phase boundaries [2,3], to local moment formation [4], nonlocal correlation effects [5,6], and various types of symmetry breaking [7][8][9][10][11][12][13]. Already in the two-band case, nontrivial crossovers and phase transitions can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we demonstrated a novel mechanism for photoenhanced excitonic order based on a cooperative effect between the e-ph coupling, the massive phase mode, and the Hartree shift. Combining photoexcitation and a reduction of the symmetry of the Hamiltonian may provide a new strategy to enhance analogous orders such as SC [58].…”
mentioning
confidence: 99%
“…S3(d) in [26]). A recent study [25] has shown that in the case of a multiorbital Hubbard model without spin-orbit coupling, s-wave spin-triplet superconductivity can appear along the spin-freezing line. The effect of the spin-orbital cross-correlation on this superconductivity will be an interesting future research topic.…”
mentioning
confidence: 99%